The opportunity costs of commuting: the value of a commuting satellite account framework with an example from Lisbon Metropolitan Area - Ferreira, João Pedro (2018)
Commuting affects regional and urban economies. It shapes urban areas, defines their relationships with neighboring regions, inten- sifies economic flows and exacerbates energy consumption and greenhouse gas emissions. This paper sets out a proposal for an innovative commuting satellite account (CSA), integrated in a multi- regional input–output model. This framework combines commuting activities with regional distribution of income, distinct household consumption structures, real estate renting activities and the energy consumption and environmental flows incorporated in the different industries. To assess the opportunity costs of commuting, the CSA framework is applied to the Lisbon Metropolitan Area. The socio- economic-environmental impacts of a scenario in which commuters become non-commuters by moving their residence to the munici- pality in which they work are estimated. The analysis indicates that: commuting, in general, induces significant economic and environ- mental opportunity costs. Finally, the adoption of policy-oriented recommendations contributing to limit sprawling in metropolitan regions is discussed.